One-pot conversion of biomass-derived xylose and furfural into levulinate esters via acid catalysis - Hu, X.; Jiang, Shengjuan; Wu, L.; Wang, Shuai; Li, Chun-Zhu (The Royal Society of Chemistry, 2017)
© The Royal Society of Chemistry.Direct conversion of biomass-derived xylose and furfural into levulinic acid, a platform molecule, via acid-catalysis has been accomplished for the first time in dimethoxymethane/methanol. Dimethoxymethane acted as an electrophile to transform furfural into 5-hydroxymethylfurfural (HMF). Methanol suppressed both the polymerisation of the sugars/furans and the Aldol condensation of levulinic acid/ester.